Exploring parent and coach relationships in youth sport: A qualitative study - O`Donnell, K.; Elliott, S. K.; Drummond, M. J. (Qualitative Research in Sport, Exercise and Health, 2022)
Extensive research recognises the complex and often conflictual nature of parents and coaches involvement in youth sport. There are very few accounts that deeply explore the nature of parent and coach relationships in the current stock of literature, even less so from a sociocultural perspective. This is significant given that the behaviours of parents and coaches can determine youth athletes` enjoyment, motivation, and psychosocial development within sport. As such, this study sought to understand how parent and coach relationships develop in an Australian youth sport context. Based on qualitative data collected from semi-structured interviews with parents (n = 10) and coaches (n = 10) in South Australia, four main themes were developed including the importance of credentials, the intermediary role, sharing goals, values, and expectations, and managing relational boundaries. The key findings suggest that parent and coach relationships are developed and shaped by broader aspects of society and culture, and beyond social exchanges with one another. It was found that this type of relationship is developed and maintained by wider discourses, historical and cultural specificity, and forms of language that reinforce a contemporaneous meaning and significance of parent and coach interactions.